Dinamika Perubahan Organisasi dan Strategi Pengelolaan Stres Guru di Madrasah Aliyah - Rahmah Rahmah; Nurbaiti Nurbaiti; Jamrizal Jamrizal; Samsu Samsu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Organizational changes in Madrasah Aliyah aim to improve the quality of education, but often give rise to challenges such as increased workload and stress for teachers. Effective stress management strategies, such as training, open communication, psychosocial support, and balanced workload arrangements, are key to helping teachers adapt to these changes. With a holistic and planned approach, Madrasah Aliyah can create a healthy work environment, support teacher well-being, and improve the quality of teaching in a sustainable manner.